(untitled) (Research, Society and Development, 2021)
Pilates is becoming one of the most indicated and sought after treatments by the elderly Brazilian population, in addition to contributing to physical and mental health, correlating with the elderly’s daily activities. Thus, the study sought information that helps to improve flexibility, muscle tone, postural balance, proprioception and thus minimize other pathologies, such as cardiorespiratory and musculoskeletal diseases, in addition to helping to reduce hospitalizations. According to this study, we can observe positive results in increasing flexibility and functionality, thus improving the postural balance of the elderly, consequently minimizing the risk of falls. In this way, the method was sought as an alternative therapeutic intervention to contribute to the quality of life of the elderly, with this the study intended a positive way to build new academic projects and dissemination to the target audience.